An interview with Marissa C. Keesler (Dental Press Editora, 2014)
Dr. Marissa Keesler attended dental school at Creighton University in Omaha, Nebraska and in 1987 received her Doctor of Dental Surgery degree with high honors. In 1989, she graduated from Marquette University with a Certificate and Master of Science degree in Orthodontics. Dr. Keesler has been an Adjunct Professor in the Marquette Graduate Orthodontic Department since 1990 and has been a guest speaker at several universities and orthodontic groups nationally and internationally. She has contributed to the development of several orthodontic textbooks in topics related to multidisciplinary treatment and the indirect bonding technique. Dr. Keesler is a member of the American Association of Orthodontists and many other local and national dental and orthodontic societies such as the Edward H. Angle Society of Orthodontists and the Pierre Fauchard Academy. She also has Diplomate status with the American Board of Orthodontics and is a graduate of the AEO Roth/Williams Center. Dr. Keesler has been in specialty practice since 1989 and has had a full-time private practice in Neenah since 1992. In 2000, she was joined by her husband, Dr. Jeffrey T. Keesler, who has a dual specialty in Prosthodontics and Orthodontics. Dr. Roberto Lima Filho